Use of multimodal imagery with precompetitive anxiety and stress of elite tennis players - Weigert Coelho, R.; Keller, B.; Kuczinski, K. M.; Ribeiro Jr., E.; de Araujo Montoro Lima, M. C.; Greboggy, D.; Facco Stefanello, J. F. (Perceptual and Motor Skills, 2012)
The effect of multimodal imagery on anxiety and perceived stress was investigated in 46 male tennis players (16 to 18 yr.; M = 17.0, SD = 0.8). There were two groups, a multimodal imagery group and a control imagery group. The quasi-experimental design included pre- and post-treatment administrations of the 27-item Competitive State Anxiety Inventory to assess anxiety and the Perceived Stress Scale to assess stress. Analysis showed a statistically significant multivariate difference between the multimodal imagery and control groups on measures of cognitive anxiety, self-confidence, and perceived stress. Imagery plays a role in handling some specific types of anxiety and stress.